2018
DOI: 10.1155/2018/1784073
|View full text |Cite
|
Sign up to set email alerts
|

Analyses of Essential Elements and Heavy Metals by Using ICP-MS in Maternal Breast Milk from Şanlıurfa, Turkey

Abstract: Maternal breast milk is a unique biological matrix that contains essential micronutrients. Potentially heavy metals may also affect infants' health and growth through maternal breast milk. The purpose of this study was to determine and compare the essential elements and heavy metals of maternal breast milk of nursery mothers residing in Şanlıurfa province, Turkey. Maternal breast milk concentrations of sodium, magnesium, phosphorus, potassium, calcium, iron, copper, zinc, arsenic, and lead were analyzed in a r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 23 publications
1
4
0
Order By: Relevance
“…The “Priority List of Substances” released in 2017 by the Agency for Toxic Substance and Disease Registry ranked Arsenic as the potentially most hazardous element to human health. The low As concentration in our HM samples was comparable to other studies performed in Sweden ( Björklund et al, 2012 ), Chile ( Castro et al, 2014 ), USA ( Carignan et al, 2015 ), Turkey ( Kılıç Altun et al, 2018 ), and Slovenia ( Jagodic et al, 2020 ; Snoj Tratnik et al, 2019 ) ( Table A2 ). However, two studies ( Bassil et al, 2018 ; Klein et al, 2017 ) showed higher mean As concentrations than reported in the present study (>2 μg/L).…”
Section: Resultssupporting
confidence: 89%
“…The “Priority List of Substances” released in 2017 by the Agency for Toxic Substance and Disease Registry ranked Arsenic as the potentially most hazardous element to human health. The low As concentration in our HM samples was comparable to other studies performed in Sweden ( Björklund et al, 2012 ), Chile ( Castro et al, 2014 ), USA ( Carignan et al, 2015 ), Turkey ( Kılıç Altun et al, 2018 ), and Slovenia ( Jagodic et al, 2020 ; Snoj Tratnik et al, 2019 ) ( Table A2 ). However, two studies ( Bassil et al, 2018 ; Klein et al, 2017 ) showed higher mean As concentrations than reported in the present study (>2 μg/L).…”
Section: Resultssupporting
confidence: 89%
“…Copper was detected at a mean concentration higher than the concentrations in other work published in Poland [30,42], Sweden [24], Portugal [26], Italy [27] and Saudi Arabia [43] but lower than those found in Nigeria [44], Greece [22] and Turkey [45]. Eighteen samples exceeded the maximum tolerable level of copper.…”
Section: Resultsmentioning
confidence: 55%
“…The mean breastmilk calcium concentration was comparable to those reported among non-malnourished lactating women elsewhere. 3,[15][16][17][18] One previous case-control study found that the mean breastmilk calcium concentration in lactating women who had infants with rickets was significantly lower compared with the control lactating women. 6 Palestinian immigrant children had lower vitamin D levels in Denmark compared with their Danish controls.…”
Section: Re Sultsmentioning
confidence: 99%